Optimization of TIG welding parameters and filler rod material selection for dissimilar aluminum alloy joints - Kasu Karthick; K. Sravanthi; S. P. Jani; D. Antony Prabu; Senthil Vadivel T.; Haiter Lenin Allasi (Journal of Materials Science: Materials in Engineering)
Abstract The objective of this research is to enhance the mechanical characteristics of aluminum alloy welds by adjusting tungsten inert as (TIG) welding parameters. Different welding parameters, such as current (150, 170, and 190 amps), gas flow rate (10, 11, and 12 l/min), and filler rod diameter (1.6, 2.0, and 2.4 mm), were systematically analyzed using the TOPSIS technique used in industries like aerospace, automotive, and construction, where precise welding control ensures aluminum alloy reliability and performance. It engages in multiparameter optimization which systematically ranks welding parameters, helping identify key factors that enhance weld quality. The response parameters selected were ultimate tensile strength (UTS), Vickers hardness, and percentage of elongation. A total of 31 microhardness readings were obtained to assess hardness distribution across the welded joints. Analysis of the results indicated that the filler rod diameter significantly influenced all response parameters. Specifically, it had the highest impact on UTS, elongation, and hardness, with contribution percentages of 48.4%, 52.6%, and 51.41%, respectively. The gas flow rate and welding current also affected these properties but to a lesser extent. ANOVA results showed that the filler rod diameter was the most critical factor, with high F-values and low P-values for each response parameter. The study concludes that optimizing filler rod diameter can substantially improve weld quality, making it the most influential parameter in achieving desired mechanical properties in TIG welding of aluminum alloys.